PROMOTING SUSTAINABLE ECONOMIC GROWTH AND INDUSTRIALISATION: SOLUTION TO MASS UNEMPLOYMENT AND POVERTY - Ogbimi, F. E. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
This paper analysed the twin-problems of unemployment and poverty. The methodology adopted in the analyses was a combination of the historical and logico-mathematical research perspectives. The results showed that the technologically advanced nations (TANs) experienced mass unemployment, low productivity, high inflation and prevalent poverty problems for many centuries before they achieved industrial revolution (IR). When they achieved the modern IR, not only did the mass unemployment problem disappear, but also, there were not enough adults persons to fill the employment openings created by the industrialisation. Consequently, industrialists resorted to employing children who worked in factories for many hours everyday, and prevented them from receiving education. Unemployment and poverty, therefore are symptoms of stagnation and lack of industrialisation (the disease). The long-term solution to mass unemployment and poverty therefore is industrialisation, for there is no industrialised nation that is poor. The short-term solution is promoting sustainable economic growth and competence-building. However, because achieving sustainable economic growth, competence-building and industrialisation are learning processes, Nigeria and other developing nations need to develop good educational systems. They should also establish suitable frameworks for training university graduates, scientists and engineers in particular in a curriculum-based scheme to acquire complementary practical skills in the economy outside campuses. This is how the poor nations can achieve sustainable growth, build-up individual and national competence, promote industrialisation and eliminate unemployment and poverty problems, speedily.